2008
DOI: 10.1111/j.1440-1789.2007.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Tanycytic ependymoma arising from the right lateral ventricle: A case report and review of the literature

Abstract: A 38-year-old man presented with a year-long history of worsening headache. Neuroradiological findings showed that a solid cystic mass occupied the right lateral ventricle. Histologically, the tumor composed of nuclear dense zones consisting of a cluster of spindle cells and fibrillary zones consisting of streaming of cell processes. The tumor cells showed the characteristics of monopolar or bipolar processes. Some tumor cell processes extended to the vessel wall and formed ill-defined perivascular rosettes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Both myxopapillary tumors found in this cohort were extramedullary and located around the filum terminale, in keeping with previous reports of the typical location of this tumor subtype [8, 21, 34]. The case of the one patient with multiple grade II tanycytic tumors demonstrates the potential for aggressive behavior possessed by ependymomas, even in a histologic subtype reported to have a good prognosis [51]. …”
Section: Discussionsupporting
confidence: 89%
“…Both myxopapillary tumors found in this cohort were extramedullary and located around the filum terminale, in keeping with previous reports of the typical location of this tumor subtype [8, 21, 34]. The case of the one patient with multiple grade II tanycytic tumors demonstrates the potential for aggressive behavior possessed by ependymomas, even in a histologic subtype reported to have a good prognosis [51]. …”
Section: Discussionsupporting
confidence: 89%
“…The prognosis of TE is associated with the patient age, tumor site and the extent of surgical resection. It has been reported that the 5-year and 10-year survival rates for TE are improved compared with those with other subtypes of ependymoma ( 33 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 1978, Friede and Pollak first described tanycytic ependymoma as a variant of ependymoma, being relatively common in the spinal cord. 11 To date, a number of tanycytic ependymomas have been described in both the cerebrum [12][13][14][15][16] and spinal cord. [17][18][19][20][21][22][23][24][25] Tanycytic ependymoma as the glial component of a cerebral ganglioglioma has also been described.…”
Section: Discussionmentioning
confidence: 99%